Navigating in chromone chemical space: discovery of novel and distinct A3 adenosine receptor ligands. Issue 96 (17th October 2015) - Cagide, F.; Gaspar, A.; Reis, J.; Chavarria, D.; Vilar, S.; Hripcsak, G.; Uriarte, E.; Kachler, S.; Klotz, K. N.; Borges, F.
<x xml:space="preserve">Abstract</x> One of the major hurdles in the development of effective drugs targeting GPCRs is finding ligands selective for a specific receptor subtype. Here we describe a potent and selective hormone-based hA3 AR ligand (Ki of 167 nM) with a remarkable selectivity.